PHYLOGENETIC RELATIONSHIP OF BAROPHILIC BACTERIA FROM NORTHWESTERN PACIFIC OCEAN - Ocky Karna Radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2001)
In order to elucidate the role of hydrostatic pressure on the distribution of marine microorganisms, deep-sea water samples from north-western Pacific Ocean were collected and used as the source of barophilic bacteria. One isolate, JTW-863 was obtained from a depth of 6000 m, while two isolates, MTW-1 and MTW-13, were obtained from a depth of 10,500 m. Phylogenetic analysis based on PCR-amplified 16S rDNA revealed that JTW-863 belonged to Moritella, while MTW-1 was mostly related to Shewanella. On the other hand, MTW-13 was affiliated with the uncultured clone NB1-d from deep environment.